Numerical simulation of pcm intergrated solar collector storage water heater - Redzuan, M. (Asian Research Publishing Network, 2017)
Solar water heater has been widely used in domestic and industrial sectors to harvest the available solar radiation daily to produce hot water. Computational analysis on performance of solar water heater has been trending up to offset the higher cost of experimental measurement. A 3D computational fluids dynamics (CFD) model was developed and validate with experimental results. The average hot water temperature simulated at 1.00PM until 5.00PM variesfrom 49.0 oC to 54.9 oC, while average PCM temperature varies from 53.0 oC to 64.8 oC. The CFD models developed shows a good agreement of 6.7 and 7.1 simulation error for hot water temperature and PCM temperature respectively. The simulation model developed can be used as a prediction tool for solar energy research and to reduce cost on development of experimental test rig for solar collector experiment.